Inhibitory effect of Capparis spinosa extracts against pathogenic bacteria - Mohsen Al - Akeidi; Angham al-Akidi; kawkab Adris (College of Education for Pure Sciences, 2012)
ABSTRACT This research was conducted to study the inhibitory activity of Capparis spinosa extracts against some pathogenic bacteria. Extracts prepared in different concentrations (200,400,500)mg/ml and agar diffusion method was used to studying this activity, also the synergism effects between plant extract and some antibiotic was studied. Results indicates that Gram positive bacteria was resistant to plant extracts while Gram negative bacteria varied in their sensitivity depending on plant part and type of bacteria. The aqueous and alcoholic extracts of plant's fruit appear to be most affective. As the concentration of plant extracts increase the activity of inhibition increase as well. In some cases plant extract activity was more effective than studied antibiotics and also result showed synergism effect between plant extract and antibiotics and some studied bacteria lost their resistance to antibiotics by this synergism phenomenon.